Effect of Workloafing, Cyberloafing and Self Efficacy on Employee Performance in Purwokerto Islamic Hospital - Eni Yulianti; Fatmah Bagis (Journal of Economics, Social, and Humanities, 2023)
This study aims to determine and analyze the effect of workload, cyberloafing and self-efficacy on employee performance at Purwokerto Islamic Hospital. The population of this research is the Employees of the Purwokerto Islamic Hospital. This study applies a quantitative approach method. The sample used in this study amounted to 153 respondents. Obtained using non-probability sampling with purposive sampling technique. The instrument used in data collection is a questionnaire with primary data measurements. The data obtained was processed using classical assumptions, hypotheses and multiple linear regression analysis with the statistical package for the social sciences (SPSS) analysis tool . The results of this study indicate that workload and self-efficacy have a positive and significant effect on employee performance and cyberloafing has a negative and significant effect on employee performance. Based on the test results of the coefficient of determination R 2 adjusted by 83.9%.